Die literêre soortlikheid van die fantasie, met spesiale verwysing na die Narnia-verhale van C.S. Lewis, die Huppelkind-reeks van W.O. Kühne en Ken jy die Kierangbos? van Freda Linde - Whitfield, Lesley (Afrikaans and Netherlandic Studies, 2016)
This study is an investigation regarding the nature of the fantasy as a literary form, with special reference to children's literature. In Chapter 1 some recent theories on fantasy are examined in order to establish a theoretical basis for the study. A model is proposed in which the fantasy element is seen as the defining quality of the fantasy tale. This element consists of the depicting of events that are by nature "outside" of reality. In Chapter 2 the theory discussed in Chapter 1 is applied to three literary works traditionally regarded as fantasies. They are: the Chronicles of Narnia by C.S. Lewis; Huppel en sy maats by W.O. Kuhne and Ken jy die Kierangbos? by Freda Linde. Although these works do not all conform to the theories discussed in Chapter 1, it can be concluded that the fantasy element is central in each one and that they can therefore be defined as fantasies. In Chapter 3 the role of symbolism in the fantasy is considered. It is found that although symbolism is often used in this literary category, it is not a distinguishing quality of the fantasy. In Chapter 4 the specified works are examined as literature for children, with the aim of determining the relation between the fantasy and children's literature. It is concluded that the nature of the fantasy as a literary form makes it especially suitable for children because of the child's perception of reality. Chapter 5 consists of a summary of the findings in the previous three chapters. In conclusion the model proposed in Chapter 1 is re-examined. Fantasy is seen as a comprehensive literary category wi th sub-categories providing for the variety of literary works classified as fantasies according to the definition proposed.